Effect of coagulant type and concentration on the yield and quality of soy-lupin tofu - Jayasena, Vijay; Tah, W.; Nasar-Abbas, Syed (Wageningen Academic Publishers, 2014)
Soy-lupin tofu samples were prepared by replacing 30% soybean with Lupin flour. Four different coagulants, i.e. calcium sulphate, calcium lactate, magnesium sulphate and magnesium chloride, were used at three different concentrations (0.3,0.4 and 0.5% w/v of the milk') to study their effect on yield and quality improvement. The results revealed that the tofu samples prepared using magnesium sulphate had higher moisture content and fresh yield than those prepared from other coagulants. The L*, a* and b* colour coordinates showed no significant differences among the samples. Fat content was affected by the type and concentration of the coagulants. Magnesium sulphates and magnesium chloride at 0.5:% level produced tofu with lower fat contents. Protein contents, however, were not affected by type or concentration of coagulant. Texture profile analysis revealed that the hardness and chewiness of samples change with the type and concentration of the coagulant whereas cohesiveness and springiness were the selected samples showed no significant differences. Based on the higher fresh yield magnesium sulphate was found to be better coagulant for soy-lupin tofu preparation.